Recent Updates on Induced Pluripotent Stem Cells in Hematological Disorders - Methichit Wattanapanitch (Stem Cells International, 2019)
Over the past decade, enormous progress has been made in the field of induced pluripotent stem cells (iPSCs). Patients’ somatic cells such as skin fibroblasts or blood cells can be used to generate disease-specific pluripotent stem cells, which have unlimited proliferation and can differentiate into all cell types of the body. Human iPSCs offer great promises and opportunities for treatments of degenerative diseases and studying disease pathology and drug screening. So far, many iPSC-derived disease models have led to the discovery of novel pathological mechanisms as well as new drugs in the pipeline that have been tested in the iPSC-derived cells for efficacy and potential toxicities. Furthermore, recent advances in genome editing technology in combination with the iPSC technology have provided a versatile platform for studying stem cell biology and regenerative medicine. In this review, an overview of iPSCs, patient-specific iPSCs for disease modeling and drug screening, applications of iPSCs and genome editing technology in hematological disorders, remaining challenges, and future perspectives of iPSCs in hematological diseases will be discussed.